Tabletiranje snovi, občutljivih na povišan tlak - Joksimović, Tatjana (Farmacevtski vestnik, 2008)
There are more and more materials that are sensitive to high pressure during tableting process. These materials include biologically active proteins, probiotics, polymorphic drugs and some excipients. Therefore tableting of these materials is performed at low pressures. Traditional excipients like microcrystalline cellulose, hyroxypropylmethyl cellulose and dicalcium phosphate dihiydrate are often unable to form stable and robust tablets at lowpressure. Excipients with greater elastic deformation are more suitable forsoft tableting. From a theoretical point of view, mechanical properties of materials are best described by parameter of general plasticity (GP). This parameter includes parameters describing materials time plasticity, pressure plasticity, elastic decompression and elastic recovery. The lower the GP of material, more suitable it is for tableting at low pressure. The correlation between GP and stability of pressure-sensitive material was found out. Excipients with low GP can reduce the transformation among different drug polymorphic forms due to tableting, they are able to prevent inactivation of incorporated enzymes, and can prevent damages of functionally coated pellets during tableting. According to literature data the most suitable excipients for soft tableting are the carrageenans.
Keywords: mehanske lastnosti; polnila; tabletiranje